Algorithms for a System of General Variational Inequalities in Banach Spaces - Jin-Hua Zhu; Shih-Sen Chang; Min Liu (Journal of Applied Mathematics)
The purpose of this paper is using Korpelevich's extragradient method to study the existence problem of solutions and approximation solvability problem for a class of systems of finite family of general nonlinear variational inequality in Banach spaces, which includes many kinds of variational inequality problems as special cases. Under suitable conditions, some existence theorems and approximation solvability theorems are proved. The results presented in the paper improve and extend some recent results.